Relationships Between Initial COVID-19 Risk Perceptions and Protective Health Behaviors: A National Survey - Bruine de Bruin, Wändi; Bennett, Daniel (American journal of preventive medicine, 2020)
Perceptions of health risks inform decisions about protective behaviors, but COVID-19 was an unfamiliar risk as it began to spread across the U.S. In the initial stage of the epidemic, authors examined perceived risks for COVID-19 infection and infection fatality and whether these risk perceptions were associated with protective behaviors. They also examined whether findings differed between later versus earlier responders. Between March 10 and March 31, 2020, a cross-sectional online survey was conducted with a nationally representative U.S. sample (n=6,684). Half responded before March 13, 2020 (versus later). Participants assessed their risks of COVID-19 infection and infection fatality (0%–100%) which were transformed into quartiles (1–4). They reported their implementation of protective behaviors like handwashing and social distancing (yes/no). Analyses were conducted in April‒May 2020. Median perceived risk was 10.00% for COVID-19 infection and 5.00% for infection fatality, but respondents showed large disagreement. An increase of 1 quartile in perceived infection risk was associated with being 1.45 times (95% CI=1.33, 1.58) more likely to report handwashing, with perceived infection fatality risk showing no significant association. When predicting social distancing behaviors such as avoiding crowds, both quartile-based risk perceptions were significant (OR=1.24, 95% CI=1.17, 1.30 for infection and OR=1.19, 95% CI=1.13, 1.26 for infection fatality). Perceived COVID-19 infection risk, protective behaviors, and their relationship increased among later (versus earlier) responders. Despite disagreements about the risks, people perceiving greater risks were more likely to implement protective behaviors—especially later (versus earlier) in March 2020. These findings have implications for risk communication.